砂拉越古晋华人饮食名称 的语言特色研究 (A Linguistic Study On The Names Of Chinese Food In Kuching, Sarawak) - Jong, Ning Oii (2018)
The theory of linguistics shows that an important component of culture, is a mirror that reflects culture, embodies a country, a nation, or a humanistic spiritual culture peculiar to a place. It is often reflected in the subtleties of social life, reflected in the real society. Therefore, specific names of food are accepted as a universal social phenomenon, reflects not only a noun, but also indicates cultural implications. Thus, the research on the topic of the names of food is important, necessary and meaningful. The scope of this study is limited to the Kuching town area in Sarawak, Malaysia. This research adopts field investigation method, literature research method, and descriptive statistics method. This research is mainly from the synchronic point of view, for an example, on-site visits to the Chinese foods stalls, collecting food signboards, publications, interview recordings and other sources in the vicinity of Kuching City. The purpose of this research is to study the language characteristics of Chinese food names in Kuching, Sarawak. This research covering the Phonological, Morphological and Semantic aspects of language. The theories of Language contact (Thomason & Kaufman, 1988) and Code-switching (Jack C Richards,2007) are predominantly used throughout this Linguistic Study on the Names of Chinese Food in Kuching, Sarawak. iv The Language characteristics of Chinese food names in Kuching Sarawak have the following characteristics: Firstly, vocabulary classification divided into general vocabulary and specific vocabulary; the existence of code-switching phenomenon; nomenclature method is mainly based on the main ingredients. Secondly, the word formation method is based on compound words; the vocabulary source is mainly inheritance words; and some from the local Sarawak Kuching regional specific words. Thirdly, three-syllable words dominated in phonetic form; texts and spoken words were inconsistent, and pronunciations were different; complex phonetic-semantic relations. Fourthly, the semantic features are mainly represented by innovation; reduction; and semantic expansion. In summary, Kuching city has produced a unique and hybrid Chinese food names under a multilingual and multicultural environment. The names of Chinese food are the product of language contact and multilingualism. With the changes and development of society, the names of Chinese food in Kuching are also undergoing great changes. The traditional Chinese food culture that originated from the original Chinese phase slowly absorbed the essence of the dietary culture of other ethnic groups and carried out local transformation and innovation, thus enriching the food culture of Chinese in Sarawak.